Adult Neurogenesis in Epileptogenesis: An Update for Preclinical Finding and Potential Clinical Translation - Chen, Liying; Wang, Yi; Chen, Zhong (Current Neuropharmacology, 2020)
Epileptogenesis refers to the process in which a normal brain becomes epileptic, and is characterized by hypersynchronous spontaneous recurrent seizures involving a complex epileptogenic network. Current available pharmacological treatment of epilepsy is generally symptomatic in controlling seizures but is not disease-modifying in epileptogenesis. Cumulative evidence suggests that adult neurogenesis, specifically in the subgranular zone of the hippocampal dentate gyrus, is crucial in epileptogenesis. In this review, we describe the pathological changes that occur in adult neurogenesis in the epileptic brain and how adult neurogenesis is involved in epileptogenesis through different interventions. This is followed by a discussion of some of the molecular signaling pathways involved in regulating adult neurogenesis, which could be potential druggable targets for epileptogenesis. Finally, we provide perspectives on some possible research directions for future studies.
Keywords: neural circuit